The Effect of Landscape Environmental Factors on Gene Flow of Red Deer (Cervus canadensis xanthopygus) in the Southern of the Greater Khingan Mountains, China - Zheng Li; Jinhao Guo; Yang Hong; Ning Zhang; Minghai Zhang (Biology, 2023)
Red deer (Cervus canadensis xanthopygus) living in the north of China are restricted and threatened due to human activities and the changes in the natural environment, which influence the dispersal and effective gene flow between different groups of red deer. Effective gene flow plays an important role in maintaining genetic diversity and structure and ensuring population health. In order to evaluate the genetic diversity level and understand the gene flow between different red deer groups, 231 fresh fecal samples were collected from the southern part of the Greater Khingan Mountains, China. A microsatellite marker was used for genetic analysis. The results showed that the genetic diversity of red deer was intermediate in this region. Significant genetic differentiation among different groups was found in the main distribution area (p < 0.01) using F-statistics and the program STRUCTURE. Different degrees of gene flow existed in red deer groups, and the roads (importance = 40.9), elevation (importance = 38.6), and settlements (importance = 14.1) exerted main effects on gene flow between red deer groups. Human-made factors should be noticed and strictly supervised in this region to avoid excessive disturbance to the normal movement of the red deer. Further conservation and management of red deer should reduce the intensity of vehicular traffic in the concentrated distribution areas of red deer, especially during the heat season. This research helps us better understand the genetic level and health status of red deer in the southern part of the Greater Khingan Mountains and provides theoretical references for protecting and restoring the red deer populations in China.